แบบแผนและเงื่อนไขของพฤติกรรมเสี่ยงทางเพศในกลุ่มผู้ติดเชื้อเอชไอวีที่มีคู่ผลเลือดเอชไอวีต่างกัน ในจังหวัดเชียงใหม่ - เยาวลักษณ์ ใจมูล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
“HIV Discordant Couples” is groups of husband and wife or couples which one of them is infected with HIV. This group is important in terms of the control and prevention of HIV propagation as they are in high risk of HIV-infection. The study was a qualitative study aims to study pattern and condition of sexual risk behavior among HIV-infected group with HIV discordant couples in Chiang Mai Province. It was considered according to the Ecology Model which was divided in 3 dimensions, 1) Intrapersonal factor, 2) Interpersonal factor, 3) Community factor. Data were collected by qualitative method from June to September, 2013 from 16 samples. The data collection tools consisted of two parts, first was a record of personal information, data were analyzed by distributed frequency and percentage. Second tool was semi-structured interview questions, analyzed data by categorizing data and summarizing main idea. Results from the study found that HIV discordant couples had pattern of sexual risk behaviors as follows. Disclosure of HIV status, everybody revealed their HIV status for their couples. Their couples also accepted and had normal daily life. For the condom use behavior, it was found that they did not use condom before they knew the HIV test results. There was a group of people who consistently used condom, however the frequency of condom use decreased when the time passed. Moreover, there was another group who never used condoms with HIV discordant couple. Reasons for not using condom were unnatural feeling, alcohol drinking, difficulties in using condom, women had no power to negotiate with men about condom use, blood test results of person found no HIV infection, and the way to represents love and loyalty. In terms of condition of sexual risk behavior among HIV-infected group with HIV discordant couples in 3 dimensions, it was found that 1) Intrapersonal factor: attitudes of HIV-infected person with HIV discordant couples affected behaviors of not using condom, although they had accurate knowledge about prevention of HIV propagation. 2) Interpersonal factor: relationship between HIV discordant couples; argument avoidance, boredom in talking about using condom, thought that condom was unnecessary for couples and tiredness from work, affected condom use behavior. However, the relationship between family and a group of friends or colleagues did not affect the use of condoms. 3) Community factor: attitudes of community toward AIDS and HIV-infected people had no relationship with sexual and condom use behavior of HIV-infected group with HIV discordant couples. Results of the study can be used to plan and seek for solutions of the problem in order to decrease sexual risk behaviors among HIV-Infected group with HIV discordant couples and prevent the propagation of HIV to others.